Silent spread of pathogens in hospital settings: a one-week molecular epidemiologic study - Elif S Tanriverdi; Yusuf Yakupogullari; Deste Ceylan; Yucel Duman; Baris Otlu (Journal of Infection in Developing Countries)
Introduction: Molecular fingerprinting analyses of the pathogens isolated from healthcare-associated infections (HAIs) in an off-outbreak period can provide important data which cannot be obtained by prospective surveillance. Such data may indicate unnoticed breaks in infection control measures and guide in determining targeted interventions or reinforcements. The study aimed to analyze the clonal relatedness of pathogens isolated from HAIs during a period when the facility}'s HAI rate remained stable.